Comparison of Low-Dose Isotretinoin and Conventional Dosing Regime for the Management of Acne Vulgaris - Ghani, Usman; Bakhtawar, Ansa; Tariq, Izma (Biological and Clinical Sciences Research Journal, 2025)
Acne vulgaris is a prevalent dermatological condition that significantly affects quality of life. Although isotretinoin is the gold-standard treatment for moderate to severe acne, its conventional dosing is often associated with considerable side effects, prompting investigation into low-dose regimens for comparable efficacy with improved tolerability. Objective: To compare the efficacy and safety of low-dose isotretinoin versus a conventional dosing regimen in patients with moderate to severe acne vulgaris. Methodology: An observational comparative study was conducted with 120 patients aged 14 years or older, equally divided into two treatment groups. Group A received conventional-dose isotretinoin (80 mg/day) while Group B received low-dose isotretinoin (20 mg/day). Acne severity was assessed at baseline using GAGS scores, with moderate acne classified as 19–30 and severe acne as 31–38. Efficacy was evaluated by calculating the percentage reduction in GAGS scores after 12 weeks, categorized as slight (<30%), moderate (30–50%), good (50–80%), or excellent (>80%). An excellent GAGS score was considered adequate. Safety was monitored through clinical assessments of common side effects (e.g., dry skin and dry eyes. Results: The low-dose group exhibited higher efficacy with 70% of patients achieving excellent improvement (>80% GAGS score reduction) compared to 45% in the conventional-dose group. Adverse effects were notably lower in the low-dose group: dry skin (8.3% vs. 16.7%) and dry eyes (10% vs. 20%). Conclusion: Low-dose isotretinoin is an effective and safer alternative to conventional dosing for moderate to severe acne.